2014
DOI: 10.1136/jnnp-2013-306553
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive educational plan for patients with epilepsy and comorbidity (EDU-COM): a pragmatic randomised trial

Abstract: A patient-tailored educational strategy is effective in reducing drug-related problems (particularly drug interactions) in epilepsy patients with chronic comorbidities, without adding significant monetary costs. Registered at ClinicalTrials.gov, identifier NCT01804322, (http://www.clinicaltrials.gov).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 27 publications
(17 reference statements)
0
17
0
Order By: Relevance
“…Of the 15 RCTs investigating educational interventions, 4 studies were LOE II, 4 studies were LOE III, and 7 studies were LOE IV. All 4 LOE II studies reported improvements in their various primary outcomes: medication adherence, epilepsy knowledge and satisfaction with information and support, medication‐related problems, and HRQOL . The LOE II studies investigated psychoeducational interventions that were delivered by specialized epilepsy nurses or trained medical doctors to individuals and included personalized information during routine visits or a general information package during a series of scheduled sessions.…”
Section: Available Evidence For Psychological Treatment Across the Epmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 15 RCTs investigating educational interventions, 4 studies were LOE II, 4 studies were LOE III, and 7 studies were LOE IV. All 4 LOE II studies reported improvements in their various primary outcomes: medication adherence, epilepsy knowledge and satisfaction with information and support, medication‐related problems, and HRQOL . The LOE II studies investigated psychoeducational interventions that were delivered by specialized epilepsy nurses or trained medical doctors to individuals and included personalized information during routine visits or a general information package during a series of scheduled sessions.…”
Section: Available Evidence For Psychological Treatment Across the Epmentioning
confidence: 99%
“…Education protocols can, for example, either be delivered en bloc as a 2-day course or in a weekly format. Half of all 14 studies investigating educational programs [53][54][55][61][62][63]66 had chosen to deliver their interventions using at least 2 sessions that were at least 1 month apart. LOE I and II studies of psychological interventions and 1 self-management intervention 89 reporting significant primary outcome results were implemented in at least 4 sessions 86 that were delivered with a maximum frequency of weekly sessions 84 and a minimum frequency of 2-3 weeks between sessions.…”
Section: Evaluation Of the Treatment Delivery And Implementation Momentioning
confidence: 99%
“…Three studies were identified that looked at the costeffectiveness of epilepsy surgery and compared it with 35 20 2 5 90.9 Beretta et al 47 15 5 7 75.0 Blais et al 36 19 2 6 90.5 Bolin et al 23 17 5 4 77.3 Bowen et al 40 22 1 4 95.7 Chisholm et al 20 16 7 4 69.6 Chisholm et al 21 14 9 4 60.9 Clements et al 39 19 4 4 82.6 Craig et al 32 12 11 4 52.2 De Kinderen et al 44 21 2 3 91.3 De Kinderen et al 43 19 1 7 95.0 Frew et al 33 16 6 5 72.7 Gharibnaseri et al 34 16 5 6 76.2 Gureje et al 22 5 17 5 22.7 Hawkins et al 29 22 0 4 100.0 Helmers et al 45 16 5 6 76.2 Jentink et al 66 31 18 5 4 78.3 Lee et al 51 22 1 4 95.7 Lee et al 52 19 3 5 86.4 Majoie et al 46 11 8 8 57.9 Maltoni and Messori 27 18 5 4 78.3 Marson et al 17 21 1 5 95.5 Noble et al 48 19 1 7 95.0 Oldham et al 42 9 11 7 45.0 Plumpton et al 49 16 6 5 72.7 Rane et al 50 4 16 7 20.0 Remak et al 16 18 5 4 78.3 Remak et al 28 16 5 6 76.2 Simoens et al 24 23 0 4 100.0 Spackman et al 30 20 3 4 87.0 Suh and Lee 37 18 4 5 81.8 Van Hout et al 15 11 11 5 50.0 Vera-Llonch et al 26 18 5 4 78.3 Verdian et al 38 23 0 4 100.0 Widjaja et al 41 18 4 5 81.8 Average quality score: 77.0 "Yes" indicates sufficiently/correctly described and conducted in the study; "No" indicates insufficient, wrong, or no information regarding the specific topic in the study; NA, not applicable. A full description of the items can be found in Appendix S2.…”
Section: Epilepsy Surgerymentioning
confidence: 99%
“…Three studies looked at the cost-effectiveness of selfmanagement interventions in adults with epilepsy. Beretta et al 47 compared a standard educational plan with usual care only (i.e., medical management). The standardized educational plan, which consisted of 1 hour of counselling patients, was administered on admission and in the same form after 1 month, as a reminder.…”
Section: Self-management Interventionsmentioning
confidence: 99%
“…There were 7 studies (29%) examining the benefit of educational interventions. All of them comprised epilepsy knowledge, advocacy topics, daily self‐management behaviors, and psychosocial aspects primarily to enhance QoL (n = 4, 57%), increase knowledge and coping, increase satisfaction of patients with information and support, or reduce drug‐related problems …”
Section: Resultsmentioning
confidence: 99%